Harnessing metabolic engineering for the production of terpenoids in cyanobacteria - Herold, Ryan A. (2020)
Cyanobacteria are photosynthetic microorganisms that can be engineered to convert carbon dioxide into a myriad of useful chemicals. Terpenoids are the largest class of natural products and have applications in a wide variety of industries including fuels, pharmaceuticals, materials, cosmetics, and flavors and fragrances. Many of these compounds can be chemically synthesized or extracted from plants, however this is often either unsustainable or economically prohibitive. An alternative method of production relies on the heterologous expression of terpene synthase enzymes in cyanobacteria, producing the desired terpenoids directly from carbon dioxide. That strategy was explored in this work, whereby a heterologous mevalonate pathway, an enhanced methylerythritol phosphate (MEP) pathway, and a heterologous artemisinin biosynthetic pathway were all designed for expression in both Synechocystis and Synechococcus. Additionally, a heterologous patchoulol synthase from Pogostemon cablin (patchouli) was expressed in a cyanobacterium for the first time. A highly sensitive GC-MS quantification method was developed for the detection of patchoulol, and patchoulol production was characterized under four different growth conditions.